Accelerated heating paper pressboard and transformer oil for transformer aging assessment - Ramizi Mohameda; Syahirah Abd Halima; Shafrida Sahranib; Mohd Aizam Talib (Fakulti Kejuruteraan ,UKM,Bangi., 2024)
Paper pressboard is one of the main insulating elements that need to be investigated in order to identify the life span of high voltage transformer. In actual condition, the pressboard insulation is sealed in an enclosed metal container and immersed in transformer oil. Over the time, the pressboard insulation will degrade its performance and some part of pressboard polymeric compounds disbursed into its surrounding oil and some parts of oil compounds absorbed into the pressboard. This phenomenon can be analyzed and measured with its degree of polymerization (DP). Where DP is a measure of the chain length of the cellulose macromolecules, and is correlated to the mechanical strength of the paper and also can be correlated to transformer aging assessment. Based on reviews and reports, heat was believed to be the main cause of pressboard degradation in high voltage transformer. The correlation of heat and DP is difficult to obtain while a transformer is under commissioning, as this would need for the transformer to fully dismantle and extract the pressboard at the point of interest; as this is impossible at any circumstances, unless the transformer has undergone forensic investigation if total failure occurred. Therefore, this paper is presenting a technique under accelerated heating process in order to investigate the correlation of degraded paper pressboard and heated transformer oil under an influenced of controlled heat. A newly pressboard paper insulation was cut into pieces and undergone heating process immersed in transformer oil with predetermined heating hours. The pressboard and oil specimens were then put under difference tests, namely DP, furan compound, oil colour, neutralization value and water saturation. The results show good flag above the average until 288 hours heating process with reducing DP value. This give an indication that the heating element was certainly the main parameter of aging process based on the correlation of test parameter versus aging time.